The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1001/jama.2019.11982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Hospital-Initiated Program Combining Transitional Care and Long-term Self-management Support on Outcomes of Patients Hospitalized With Chronic Obstructive Pulmonary Disease

Abstract: IMPORTANCEPatients hospitalized for chronic obstructive pulmonary disease (COPD) exacerbations have high rehospitalization rates and reduced quality of life.OBJECTIVE To evaluate whether a hospital-initiated program that combined transition and long-term self-management support for patients hospitalized due to COPD and their family caregivers can improve outcomes.DESIGN, SETTING, AND PARTICIPANTS Single-site randomized clinical trial conducted in Baltimore, Maryland, with 240 participants. Participants were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
1
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(134 citation statements)
references
References 30 publications
3
103
1
3
Order By: Relevance
“…Aboumatar and colleagues3 suggested a similar rationale for the backfire effect in their study. In post-hoc subgroup analyses performed after discovery of the coding error, it was noted that the increase in COPD-related acute care events was identified in patients with high activation status (the patient’s knowledge, skill, and confidence in managing one’s own health).…”
Section: Effect Of a Hospital-initiated Program Combining Transitionamentioning
confidence: 76%
See 1 more Smart Citation
“…Aboumatar and colleagues3 suggested a similar rationale for the backfire effect in their study. In post-hoc subgroup analyses performed after discovery of the coding error, it was noted that the increase in COPD-related acute care events was identified in patients with high activation status (the patient’s knowledge, skill, and confidence in managing one’s own health).…”
Section: Effect Of a Hospital-initiated Program Combining Transitionamentioning
confidence: 76%
“…Aboumatar and colleagues3 sought to understand the impact of combining a transitional care programme with self-management support on COPD-related acute care events (hospitalisations and emergency department (ED) visits) and health-related quality of life (HRQL) among patients hospitalised with COPD. Specifically the intervention included the following three components:…”
Section: Effect Of a Hospital-initiated Program Combining Transitionamentioning
confidence: 99%
“…Interventions to improve care at hospital discharge The literature regarding interventions to improve the continuity of care for patients with respiratory disease is dominated by studies of COPD, and the evidence for improved outcomes in this group is mixed. Aboumatar et al [38] recently undertook a randomised controlled trial of a 3-month hospitalinitiated intervention for patients recruited at hospitalisation due to COPD that comprised three components: 1) individualised self-management support (e.g. support to take medications correctly, recognise exacerbation symptoms and enact an action plan), 2) facilitated access to treatment services in the community and 3) transitional support aiming to ensure patients and their caregivers understood the post-discharge plan.…”
Section: Can Improving Continuity Of Care At Hospital Discharge Impromentioning
confidence: 99%
“…While unexpected there are now several trials in chronic respiratory disease to have reported adverse outcome for 'lifestyle or self-management' interventions. [4][5][6][7] It is difficult to appreciate a potential causal mechanism in these various trials, especially when adverse signals were temporally separate from the interventional period. 4,6 However, with several published reports potential safety concerns cannot be ignored.…”
mentioning
confidence: 99%
“…Imbalances in disease severity may also help explain worse outcomes in intervention groups, with significantly worse functional impairment, 4 respiratory failure and cardiac co-morbidity, 7 and lung function 6 reported, respectively. None of these trials stratified their randomisation on any markers of disease severity.…”
mentioning
confidence: 99%